Geodiversity and endemism in the iconic Australian Pilbara region: a review of landscape evolution and biotic response in an ancient refugium. (12th February 2013) - Pepper, Mitzy; Doughty, Paul; Keogh, J. Scott; Ebach, Malte
Abstract Aim We review the biogeography of the Pilbara, synthesize information on the geological and landscape history of this region and surrounds, and assess fine‐scale genetic structure across multiple taxa to examine hypotheses concerning the distribution of genetic lineages. We use this to provide a baseline for future biological studies in an ancient area of endemism. Location The Pilbara region, Western Australia. Methods Literature is summarized, including the history of Pilbara landscapes and climate, and previous biogeographical work. We used mitochondrial DNA phylogenetic datasets of seven co‐distributed gecko (diplodactyline and gekkonine) lineages to assess the monophyly of Pilbara lineages, and concordance with geological and habitat divisions. Results The Pilbara harbours taxa genetically distinct from their non‐Pilbara relatives, despite close geographical proximity of populations. This is emphasized at the eastern and southern margins of the Pilbara, where habitat gradients are pronounced. In contrast, the northern margin, where sandy substrates of the Pilbara meet the dunes of the northern deserts, exhibits little genetic differentiation. Within the Pilbara, diversification patterns are idiosyncratic and may reflect species‐specific ecological differences. However, a repeated north/south partitioning of genetic diversity is evident across taxa. An additional emerging pattern is an east/west genetic division in the northern Pilbara, which may relate to major drainage divides and geological discontinuities associated with east and west Pilbara terrains. Main conclusions The Pilbara is an area of exceptionally high biotic diversity and endemism. The broader biogeographical patterns revealed in our molecular analyses are consistent with those recently identified using species richness patterns of invertebrates. Future studies of additional taxa using multiple molecular markers will provide the means to test and refine the biogeographical hypotheses presented here. Understanding the biogeography of the Pilbara and the partitioning of genetic diversity across the ancient and heterogeneous landscape is of paramount importance in the face of rapidly expanding economic and developmental pressures.